2020
DOI: 10.3389/fimmu.2020.01978
|View full text |Cite
|
Sign up to set email alerts
|

C-Reactive Protein Causes Blood Pressure Drop in Rabbits and Induces Intracellular Calcium Signaling

Abstract: Systemic diseases characterized by elevated levels of C-reactive protein (CRP), such as sepsis or systemic inflammatory response syndrome, are usually associated with hardly controllable haemodynamic instability. We therefore investigated whether CRP itself influences blood pressure and heart rate. Immediately after intravenous injection of purified human CRP (3.5 mg CRP/kg body weight) into anesthetized rabbits, blood pressure dropped critically in all animals, while control animals injected with bovine serum… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 44 publications
(35 reference statements)
2
9
0
Order By: Relevance
“…One of these recent studies showed a direct, quick and extreme effect of CRP on blood pressure in rabbits (61). Human CRP was intravenously injected in vivo to reach a level of 50 mg/L.…”
Section: Crp Has An Effect On Blood Pressurementioning
confidence: 99%
See 1 more Smart Citation
“…One of these recent studies showed a direct, quick and extreme effect of CRP on blood pressure in rabbits (61). Human CRP was intravenously injected in vivo to reach a level of 50 mg/L.…”
Section: Crp Has An Effect On Blood Pressurementioning
confidence: 99%
“…After seeing such a dramatic drop in blood pressure the influence of CRP on AR signal transduction was investigated in vitro (61). ARs signal via calcium (Ca 2+ ) as second messenger was measured in real-time.…”
Section: Crp Has An Effect On Blood Pressurementioning
confidence: 99%
“…Publications in recent years showed that CRP is more than a biomarker and affects both physiological and pathological processes [5,[7][8][9]. The direct influence of CRP on the cardiovascular system of rabbits has been reported recently [10]. Here, the infusion of human CRP led to a sharp drop in blood pressure within seconds, while the heart rate was not affected.…”
Section: Introductionmentioning
confidence: 79%
“…Human CRP (Pentracor, Hennigsdorf, Germany) was purified from human pooled plasma with a selective CRP-binding matrix as described elsewhere in detail [10]. Endotoxin contamination was avoided, and CRP was stored in its native, pentameric form.…”
Section: Pharmacological Agonists and Crpmentioning
confidence: 99%
See 1 more Smart Citation